Validity Of The Kinetic Langmuir's Law For The Volatilization Of Metallic Elements In Vacuum Metallurgy: A Numerical Approach - J. P. Bellot (The Minerals, Metals and Materials Society, 1996)
During the non-ferrous metal processing, the melting step under vacuum or under rarefied gas leads to volatile metal losses. It is the case of the metallurgical processing of the nickel-based, titanium-based or zirconium-based alloys where the evaporation losses don't allow a sufficient control of the alloy chemical composition. A theoretical approach has been carried out involving both a continuum description in the liquid phase and a molecular approach in the rarefied gas phase. The finite volume method is used in order to solve the coupled transport equationsin the liquid, whereas the Boltzmann equation is modelled by using a Monte Carlo method. At the liquid metal and metallic vapor interface, the volatilization and recondensation fluxes link up the two calculations. Simulation results are given for the melting and refining of reactive metals such as titanium alloys where the control of the chemical composition remains a major difficulty. The validity of the kinetic Langmuir's law is discussed for different operating conditions.